Insertion of nursing professionals in the management of materials in a teaching hospital of Paraná - Raísa Gabrielle dos Santos Andrade; Priscila Conde Bogo; Nelsi Salete Tonini; Fabiana Gonçalves de Oliveira Azevedo Matos; Debora Cristina Ignácio Alves (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objectives: To analyze the perception of nursing professionals about their insertion in the material management process in hospital units. Methods: Exploratory study with a qualitative approach carried out in a university hospital in Paraná. Data collection was carried out between October and December 2019, through semi-structured interviews recorded in audio. The data were transcribed and submitted to thematic content analysis. Results: 35 nursing professionals participated in the study. From the speeches, four categories emerged: Participation in the process of planning and provision of materials; Sizing of resources in the institution; Participation in the quality control of materials; and Difficulties confronted in the material management process. Conclusion: The results indicate that nursing professionals have a low participation in the material management process and infer that they actively participate only in the quality control process through evaluations and notifications.